Cold Plasma Treatment of Sunflower Seeds Modulates Plant-Associated Microbiome and Stimulates Root and Lateral Organ Growth - Tamošiūnė, Inga; Gelvonauskienė, Dalia; Haimi, Perttu; Mildažienė, Vida; Koga, Kazunori; Shiratani, Masaharu; Baniulis, Danas (Frontiers in Plant Science, 2020)
Cold atmospheric pressure (CP) plasma irradiation of seeds has been shown to promote plant growth, but the molecular basis of this phenomenon is poorly understood. In our study, optimum irradiation of common sunflower seeds using a dielectric barrier discharge CP device stimulated growth of sunflower lateral organs and roots by 9-14 % compared to the control. Metagenomic analysis revealed that the structure of plant-associated bacterial assembly was greatly modified upon CP treatment and could be attributed to the antimicrobial effect of CP-generated reactive species. The treatment resulted in the domination of spore forming Mycobacterium sp. in the above-ground tissues of the seedlings. While the overall bacterial diversity in the roots was barely affected, the CP-induced shift in microbial composition is the likely basis for the observed seedling root growth stimulation and the long-term effect on lateral organ growth and could be mediated by increase in water uptake and/or direct root signaling. Low amplitude protein abundance differences were detected in the roots of the emerging seedlings that are characteristic to low intensity stress stimuli response and could be linked to the changes in plant-associated microbiome upon CP treatment.